Kidney Exchange Program Reporting Standards: Evidence-Based Consensus From Europe - Smeulders, Bart; Mankowski, Michal A.; van de Klundert, Joris (Frontiers in Public Health, 2021)
Background Kidney Exchange Programs can play an important role to increase access to the life saving and most cost-effective treatment for End Stage Renal Disease. The rise of national KEPs in Europe brings a need for standardized performance reporting to facilitate the development of an international evidence base on program practices. Methods We systematically searched and reviewed the literature to extract kidney exchange program performance measures. Reported measures were initially categorized as structure, process, and outcome measures. Expert feedback was used to redefine categories and extend the set of measures to be considered. Using the Delphi method and a panel of ten experts, the resulting measures were subsequently classified as mandatory (Base set), optional (Extended set), or deleted. Results Out of the initial 1668 articles identified by systematic literature search, 21 European publications on kidney exchange programs were included to collect performance measures, accompanied by three national program reports. The final measurement categories were Context, Population, Enrollment, Matching, Transplantation, and Outcomes. The set of performance measures resulting from the literature review was modified and classified as mandatory or optional. The resulting Base set and Extended set form the kidney exchange program reporting standard. Conclusions The evidence-based and consensus-based kidney exchange program reporting standard can harmonize practical and scientific reporting on kidney exchange programs, thus facilitating the advancement of national programs. In addition, the kidney exchange program reporting standard can promote and align cross-national programs.